Dampak Perhatian Orang Tua Terhadap Perkembangan Akhlak Anak - Windi Alya Ramadhani; Nurul Aini; Zahara Tulhusni; Wismanto Wismanto; Safa Fakhlef (Jurnal Budi Pekerti Agama Islam, 2024)
Morals are one of the main components of Islam, which include lessons about actions or manners. Through this moral education, good morality will actually be formed in children, respectful attitudes towards others and older people, respecting colleagues and respecting other people's opinions. In other words, morals can be called part of Islamic teachings which regulate the way humans behave. . In conversation, morals regulate what is considered good and bad. The aim of this research is to find out how parents pay attention to their children's morals in Islamic teachings and direct their children's attitudes and behavior. This research uses a qualitative method that emphasizes in-depth observation by analyzing more comprehensive literature. The results of this research show that parents have a very big influence on the formation of children's morals. Therefore, the real responsibility and role of parents in developing children's morals is to guide, teach and set a good example for their children.